Synapsin Condensates Recruit alpha-Synuclein. Issue 12 (11th June 2021) - Hoffmann, Christian; Sansevrino, Roberto; Morabito, Giuseppe; Logan, Chinyere; Vabulas, R. Martin; Ulusoy, Ayse; Ganzella, Marcelo; Milovanovic, Dragomir
Graphical abstract: Highlights: This study examines how α-synuclein affects the liquid phase of synapsin and SVs. A phase of synapsin 1 sequesters α-synuclein. SVs act as catalyzers for the phase separation of synapsin 1 and α-synuclein. At physiological conditions, α-synuclein alone cannot induce a liquid phase of SVs. The excess of α-synuclein slows down the rate of synapsin/SV condensate formation. Abstract: Neurotransmission relies on the tight spatial and temporal regulation of the synaptic vesicle (SV) cycle. Nerve terminals contain hundreds of SVs that form tight clusters. These clusters represent a distinct liquid phase in which one component of the phase are SVs and the other synapsin 1, a highly abundant synaptic protein. Another major family of disordered proteins at the presynapse includes synucleins, most notably α-synuclein. The precise physiological role of α-synuclein in synaptic physiology remains elusive, albeit its role has been implicated in nearly all steps of the SV cycle. To determine the effect of α-synuclein on the synapsin phase, we employ the reconstitution approach using natively purified SVs from rat brains and the heterologous cell system to generate synapsin condensates. We demonstrate that synapsin condensates recruit α-synuclein, and while enriched into these synapsin condensates, α-synuclein still maintains its high mobility. The presence of SVs enhances the rate of synapsin/α-synuclein condensation, suggesting that SVs act as catalyzers for the formation of synapsin condensates. Notably, at physiological salt and protein concentrations, α-synuclein alone is not able to cluster isolated SVs. Excess of α-synuclein disrupts the kinetics of synapsin/SV condensate formation, indicating that the molar ratio between synapsin and α-synuclein is important in assembling the functional condensates of SVs. Understanding the molecular mechanism of α-synuclein interactions at the nerve terminals is crucial for clarifying the pathogenesis of synucleinopathies, where α-synuclein, synaptic proteins and lipid organelles all accumulate as insoluble intracellular inclusions.